Portable mood mapping: the validity and reliability of analog scale displays for mood assessment via hand-held computer - Kreindler, David; Levitt, Anthony; Woolridge, Nicholas; Lumsden, Charles J. (Psychiatry research, 2003)
The long-term natural time course of mood change remains poorly understood, and improved methods that assay multiple mood symptoms quickly and reliably are crucial to further progress. This study describes the reliability and validity of the new visual analog scale (VAS) display method for a recently developed 19-item VAS-based mood questionnaire, the VMQ, administered via hand-held computer (HHC). The effect of the smaller HHC screen size on accuracy and precision of VAS completion was investigated in 28 subjects using 4- and 10-cm paper-based VASs to indicate six specified dates within the year. The influence of digital vs. paper medium was then tested in 39 subjects who completed the same task, using 10-cm paper and 4-cm HHC-based VASs. Test–retest reliability was evaluated in 29 subjects who completed the questionnaire on a HHC twice, 10 min apart. Since the HHC presents VMQ scales with text anchor orientation set randomly, we also considered whether subjects might inadvertently transpose responses on the HHC. We found that reducing VAS size produced no significant loss of response precision or accuracy in subject response. Moreover, there was no significant loss of accuracy or precision between 10-cm paper and 4-cm HHC-based versions of the VAS. HHC-based items also demonstrated excellent test–retest reliability, with excellent values of Cronbach's alpha. The transposition error rate was negligible (0.27%). Our study provides initial evidence that the HHC-based VAS display used in the VMQ is a reliable and valid tool for comprehensive collection of analog mood scale data.